Implementasi Rekam Medis Elektronik dengan Sistem Pendukung Keputusan Klinis - Feby Erawantini; Nugroho Setyo Wibowo (Jurnal Teknologi Informasi dan Terapan, 2019)
Abstract— the community has the right to get quality and affordable health services. One effort to realize quality health services is the electronic medical record. The RME application is expected to be integrated between health services and has a function as a clinical decision support system. The purpose of this study is to implement the RME application in the educational clinic and evaluate the user's satisfaction about the RME application has been implemented. The method used for RME implementation was parallel implementation and evaluation of user satisfaction by the end user computing satisfaction method. Implementation of the RME application was carried out for 2 months in the educational clinic, from September to October 2019. The study involved 2 doctors, 1 registration officer, 2 nurses and 1 pharmacy officer. The results of RME application research can be implemented in educational clinic, RME applications with clinical decision support system in the form of blood pressure, risk of Diabetes Mellitus, risk of stroke, interaction of drug content with a history of allergies, as well as abnormal warnings of laboratory and radiological examination results.